2013
DOI: 10.1371/journal.pone.0055320
|View full text |Cite
|
Sign up to set email alerts
|

The PE16 (Rv1430) of Mycobacterium tuberculosis Is an Esterase Belonging to Serine Hydrolase Superfamily of Proteins

Abstract: The PE and PPE multigene families, first discovered during the sequencing of M. tuberculosis H37Rv genome are responsible for antigenic variation and have been shown to induce increased humoral and cell mediated immune response in the host. Using the bioinformatics tools, we had earlier reported that the 225 amino acid residue PE-PPE domain (Pfam: PF08237) common to some PE and PPE proteins has a “serine α/β hydrolase” fold and conserved Ser, Asp and His catalytic triad characteristic of lipase, esterase and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…These secreted proteins are named after several highly conserved residues in their characteristic N‐terminal motifs: proline‐glutamic acid (PE) and proline‐proline‐glutamic acid (PPE) (Cole et al ., ). The C‐terminal domains of both PE and PPE proteins can be extremely long and some carry functional domains such as lipase (Deb et al ., ; Mishra et al ., ; Daleke et al ., ), aspartic protease (Barathy and Suguna, ) and serine hydrolase (Sultana et al ., 2011; 2013) domains. Although the precise function of these proteins is largely unknown, it has been demonstrated that various PE/PPE proteins are associated with virulence and persistence in the host (Sampson, ).…”
Section: Introductionmentioning
confidence: 99%
“…These secreted proteins are named after several highly conserved residues in their characteristic N‐terminal motifs: proline‐glutamic acid (PE) and proline‐proline‐glutamic acid (PPE) (Cole et al ., ). The C‐terminal domains of both PE and PPE proteins can be extremely long and some carry functional domains such as lipase (Deb et al ., ; Mishra et al ., ; Daleke et al ., ), aspartic protease (Barathy and Suguna, ) and serine hydrolase (Sultana et al ., 2011; 2013) domains. Although the precise function of these proteins is largely unknown, it has been demonstrated that various PE/PPE proteins are associated with virulence and persistence in the host (Sampson, ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of PE and PPE proteins contain relatively conserved N-terminal domains and C-terminal segments of variable length and sequence (Cole et al, 1998; Gey van Pittius et al, 2006). The function of PE and PPE C-terminal domains is largely unknown, although some of the PE and PPE proteins carry functional lipase and protease domains (Mishra et al, 2008; Daleke et al, 2011; Sultana et al, 2011; Sultana et al, 2013). The conserved structure of the PE–PPE N-terminal domains is important for PE–PPE heterodimer folding (Strong et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a conserved serine hydrolase fold has been identified in several PE and PPE proteins (27). One of these proteins, PE16, has in vitro esterase activity against short-chain fatty acid esters (28). These observations suggest that some PE and PPE proteins have specific enzyme activities that could be important for M. tuberculosis metabolism and physiology.…”
mentioning
confidence: 99%